The Legal Handling of Digital Accessibility: a Comparison of Evaluation and Policy Approaches in Federal-Level Cases in Brazil and the United States - Mateus, Delvani Antônio; da Silva, Fábio Aparecido Cândido; Rigatto, Silvia Helena; da Silva, Tiago Silva; Parreira Júnior, Paulo Afonso; Souza, Maurício Ronny de Almeida; Freire, André Pimenta (Journal of the Brazilian Computer Society, 2024)
Countries in the Global South still have less well-established procedures and resources to enact public policies and surveillance of digital accessibility. This paper presents a comparative study on the legal handling of digital accessibility in one country in the Global North and one in the Global South – the United States and Brazil. The study analyzed federal-level procedures handled by government surveillance bodies concerning public and private organizations, involving 26 cases in Brazil and 124 in the United States. The results showed that most cases in Brazil were finalized based on automated accessibility evaluations and with little evidence of long-term actions for sustained accessibility. All cases analyzed from the United States resulted in settlement agreements leading to medium to long-term initiatives, which covered continuous verification of conformance to accessibility standards and, in many cases, demanded inspections by accessibility specialists and tests with users with disabilities. The paper discusses the implications of including effective accessibility evaluation methods and long-term solutions in legal cases.